Characteristic of Redistilled Liquid Smoke Pyrolized from Different Type of Wood as A Natural Preservative for Fishery Products - Wantan Nainggolan; Tjipto Leksono; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was purposed to observe the characteristic of distilled liquid smoke pyrolized from different types of firewood as a natural preservative for fishery products. The firewood as the main material for producing liquid smoke were kandis (Garcinia xanthocymus) wood, laban (Vitex pinanta) wood, ubar (Eugenia sp) wood and timah (Elaeo sp) wood. The pyrolysis of each type of firewood was producing 35% - 43% liquid smoke. The liquid smoke was then purified by using distillation method and was analyzed for their physico-chemical characteristics and inhibition test of bacterias Staphylococcus aureus, Escherichia coli dan TPC. The results showed that the distillation of crude liquid smoke was yielding 89-92% pure distilled liquid smoke. The distilled liquid smoke contained about 1.54-3.31% phenols, 8.96-10.66% acids, and 11.40-21.15% carbonyl. They had the capacity of antioxidant activity around 93.95-94.56%, while the result of disk diffusion susceptibility test to bacteria showed that the liquid smoke can inhibit the growth of bacterias at the lowest concentration of 3.13%.Keyword : antioxidant, distillation, liquid smoke, pyrolized, purification